Perioperative and short-term outcomes of laparoscopic liver resection for recurrent hepatocellular carcinoma: A retrospective study comparing open hepatectomy - Bao, Dandan; Hu, Yiren; Zhang, Chenghao; Jin, Yibang; Wang, Pengwei; Lin, Yinfeng; Wang, Wei; Shan, Yunfeng (Frontiers in Oncology, 2022)
Background To compare the perioperative and short-term outcomes of laparoscopic liver resection (LLR) and open liver resection (OLR) in recurrent hepatocellular carcinoma (rHCC) based on propensity score matching (PSM) to investigate therapeutic safety, efficacy, and value for clinical application. Methods Forty-nine patients with rHCC who underwent surgery at Wenzhou People’s Hospital between January 2017 and March 2022 were retrospectively analyzed and classified into LLR (n=30) and OLR (n=22) cases based on the surgical method. Thirty-eight patients were screened using PSM for data analysis to compare basic clinical characteristics, perioperative outcomes, and postoperative recurrence in both groups. Results Before PSM, the tumour diameter was larger, tumor staging (BCLC staging system), intraoperative blood loss, units of blood transfused, constituent ratio of liver cirrhosis, incidence of MVI and intravascular tumour thrombus and postoperative complication were higher, and duration of hospital stay was significantly longer in the OLR group compared to those in the LLR group (p < 0.05). After PSM, there were no significant differences regarding tumour diameter, MVI incidence, blood transfusion amount or postoperative complication rate in the LLR and OLR groups. The tumor staging, incidence of vascular cancer thrombus, intraoperative blood loss and postoperative duration of hospitalisation were significantly higher in the OLR group than in the LLR group (p<0.05). The difference in recurrence-free survival (RFS) between the two groups was not statistically significant (p = 0.383). Conclusion LLR for recurrent hepatocellular carcinoma can reduce intraoperative blood loss and postoperative complication rate, shorten the duration of hospitalisation, and is superior to OLR regarding perioperative and short-term efficacy, demonstrating good safety and feasibility.